Prognostic Value of Cardiac Magnetic Resonance in Assessing Right Ventricular Strain in Cardiovascular Disease: A Systematic Review and Meta-Analysis - Bo, K.; Zhou, Z.; Sun, Zhonghua; Gao, Y.; Zhang, H.; Wang, H.; Liu, T.; Xu, L. (MedReviews, 2022)
Objective: To evaluate the prognostic value of cardiac magnetic resonance (CMR) imaging in assessing right ventricular strain via meta-analysis of current literature. Background: Right ventricular strain recorded with CMR serves as a novel indicator to quantify myocardial deformation. Although several studies have reported the predictive value of right ventricular strain determined using CMR, their validity is limited by small sample size and low event number. Methods: Embase, Medline and Web of Science were searched for studies assessing the prognostic value of myocardial strain. The primary endpoint was a composite of all-cause mortality, cardiovascular death, aborted sudden cardiac death, heart transplantation and heart failure admissions. Results: A total of 14 studies met the selection criteria and were included in the analysis (n = 3239 adults). The random-effects model showed the association of parameters of right ventricular strain with major adverse cardiac events. Absolute value of right ventricular global longitudinal strain was negatively correlated with right ventricular ejection fraction (hazard ratio: 1.07, 95% confidence interval: 1.05–1.08; p = 0.013). Despite the small number of studies, right ventricular radial strain, right ventricular circumferential strain and right ventricular long-axis strain displayed potential prognostic value. Conclusions: Right ventricular strain measured with CMR is an effective prognostic indicator for cardiovascular disease.